Numerical analysis on Buried pipes protected by combination of geocell reinforcement and rubber-soil mixture - Tavakoli Mehrjardi, Gh.; Moghaddas Tafreshi, S.N.; Dawson, Andrew (Iranian Society of Civil Engineers, 2015)
A numerical simulation of laboratory model tests was carried out to develop an understanding of the behaviour of pipes in a trench prepared with 3-Dimensional reinforced (namely "geocell-reinforced" in the present study) sand and rubber-soil mixtures, under repeated loadings. The study reports overall performance of buried pipes in different conditions of pipe-trench installations and the influence of pipe stiffness on backfill settlements, stress distribution in the trench depth and stress distribution along the pipe's longitudinal axis. Good agreements between the numerical results and experimental results were observed. The results demonstrate that combined use of the geocell layer and rubber-soil mixture can reduce soil surface settlement and pipe deflection and eventually provide a secure condition for buried pipe even under strong repeated loads.